Materialidade e imaterialidade na transformação de residências particulares em patrimônio cultural: Hilda Hilst e a Casa do Sol - Rodriguez, Mariana Cerqueira [UNIFESP] (2015)
The main objective of the present research is to understand the processes of transformation of private dwellings in Cultural Heritage as a central focus the analysis of ?Casa do Sol?, residence of the writer Hilda Hilst, registered in 2011 by the Defense Council of the Cultural Heritage of Campinas (CONDEPACC). In order to better achieve the proposed objective, the methodology intended to raise the various aspects of the context of the property construction, the trajectory, the development of the acquis, the legal aspects and functional transformations that experienced on the particular passage to a place of memory. In each group of documents sought to aggregate and confront the documents relating to the strategies used for the preparation, insertion and acceptance of the ?Casa do Sol? as part of the legacy of Hilda Hilst. The literature review concerning the extension movement of preservation practices, analysis of material culture available in the environment and identification of intended agents, make up the triad needed to understand the broader context of this registration of the ?Casa do Sol?. This research allowed us to conclude that the interventions were subject the heritage of this house bring up important historical evidence with respect to a single social setting, a chain of relationships that sustain the material and immaterial dimension of a complex and dynamic process. The intentions of the agents responsible for the functional and symbolic transformation that the residence passed become fundamental in this perspective, since the house is a ?musealized space? used by a group of agents as an instrument of mediation and negotiations of meaning, whose materiality is mobilized to meet specific demands in the present. Understanding the formation of Heritage through interpretation, ordering and exhibition of material culture, can explain a wider context of social disputes over memory and demonstrate how the places and objects behave as supporters of a permanent process of construction and reconstruction of the identities in contemporary society.